Partisipasi Masyarakat Dalam Upaya Melestarikan Tari Kuda Lumping Di Desa Marga Sakti Kecamatan Padang Jaya Kabupaten Bengkulu Utara - Yulanda, Intan; Iqbal, Moch. (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
Community participation plays an important role in cultural preservation efforts, including traditional dances such as Kuda Lumping. This research aims to analyze the participation of the people of Marga Sakti Village, Padang Jaya District, North Bengkulu Regency, in preserving the Kuda Lumping dance. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews and documentation studies. The research results show that community participation in preserving the Kuda Lumping dance takes various forms, such as direct involvement in performances, provision of facilities and infrastructure, as well as efforts to transmit cultural values to the younger generation. Factors driving community participation include a sense of belonging to local culture, support from the local government, and awareness of the importance of preserving cultural heritage. However, challenges such as the lack of player regeneration and lack of funding are still obstacles. This study concludes that active community participation is the main key in maintaining the continuity of the Kuda Lumping dance as a cultural heritage.